KONVERSI TANAMAN KOMODITI (KEDELAI KE PADI SAWAH) TERHADAP PENINGKATAN PENDAPATAN PETANI DI DESA HIALU KECAMATAN LANDAWE KABUPATEN KONAWE UTARA - Kadek Dwi Saputra; Yani Taufik; Nur Isiyana Wianti (Universitas Halu Oleo, 2022)
This research is motivated by the occurrence of three crop conversions that are still being carried out by farmers. The crop substitution carried out by transmigrant farmers started from cassava and others (1994) to soybeans (2004), then soybeans to corn plants (2015), and corn plants to lowland rice (2016). This change in crop types was caused by several factors such as the availability of market access for soybean cultivation, the local government program to make North Konawe a maize self-sufficiency area but failed, and the availability of an abundance of water to carry out lowland rice farming activities. The purpose of this study was to determine the type of crop conversion carried out by farmers in Hialu Village, to determine the economic impact of crop conversion in Hialu Village, and to determine the social impact of crop conversion in Hialu Village. The determination of the research area was carried out purposively (deliberately) on the consideration of the people in Hialu Village to convert crops from soybeans to lowland rice, and no research has been carried out on the topic of crop conversion. The sample in this study amounted to 23 farmers from a total of 78 populations. Data analysis used quantitative description analysis and cross tabulation. The results showed that the type of crop conversion carried out by farmers was a type of transition from one type of plant to another, the economic impact was an increase in income, the social impact was a decrease in the level of social solidarity and agrarian conflict, but on the other hand there was an increase in conflict due to the conversion of crops in terms of seizure. irrigation water.